Primary Cilia as Signaling Hubs in Health and Disease. Issue 1 (16th November 2018) - Nishimura, Yuhei; Kasahara, Kousuke; Shiromizu, Takashi; Watanabe, Masatoshi; Inagaki, Masaki
Abstract: Primary cilia detect extracellular cues and transduce these signals into cells to regulate proliferation, migration, and differentiation. Here, the function of primary cilia as signaling hubs of growth factors and morphogens is in focus. First, the molecular mechanisms regulating the assembly and disassembly of primary cilia are described. Then, the role of primary cilia in mediating growth factor and morphogen signaling to maintain human health and the potential mechanisms by which defects in these pathways contribute to human diseases, such as ciliopathy, obesity, and cancer are described. Furthermore, a novel signaling pathway by which certain growth factors stimulate cell proliferation through suppression of ciliogenesis is also described, suggesting novel therapeutic targets in cancer. Abstract : Primary cilia, nonmotile antenna‐like structures, detect extracellular cues and transduce these signals into cells to regulate their proliferation, migration, and differentiation. Here, how primary cilia work as signaling hubs of growth factors and morphogens to maintain human health and how their defects contribute to human diseases, such as ciliopathy, obesity, and cancer are reviewed.